The Genus Alistipes: Gut Bacteria With Emerging Implications to Inflammation, Cancer, and Mental Health - Parker, Bianca J.; Wearsch, Pamela A.; Veloo, Alida C. M.; Rodriguez-Palacios, Alex (Frontiers in Immunology, 2020)
Alistipes is a relatively new genus of bacteria isolated primarily from medical clinical samples, although at a low rate compared to other genus members of the Bacteroidetes phylum, which are highly relevant in dysbiosis and disease. According to the taxonomy database at The National Center for Biotechnology Information, the genus consists of thirteen species: A. finegoldii, A. putredinis, A. onderdonkii, A. shahii, A. indistinctus, A. senegalensis, A. timonensis, A. obesi, A. ihumii, A. inops, A. megaguti, A. provencensis, and A. massiliensis. Although typically isolated from the human gut microbiome various species of this genus have been isolated from patients suffering from appendicitis, and abdominal and rectal abscess. It is possible that as Alistipes spp. emerge, their identification in clinical samples may be underrepresented as novel MS-TOF methods may not be fully capable to discriminate distinct species as separate since it will require the upgrading of MS-TOF identification databases. In terms of pathogenicity, there is contrasting evidence indicating that Alistipes may have protective effects against some diseases, including liver fibrosis, colitis, cancer immunotherapy, and cardiovascular disease. In contrast, other studies indicate Alistipes is pathogenic in colorectal cancer and is associated with mental signs of depression. Gut dysbiosis seems to play a role in determining the compositional abundance of Alistipes in the feces (e.g., in nonalcoholic steatohepatitis, hepatic encephalopathy, and liver fibrosis). Since Alistipes is a relatively recent sub-branch genus of the Bacteroidetes phylum, and since Bacteroidetes are commonly associated with chronic intestinal inflammation, this narrative review illustrates emerging immunological and mechanistic implications by which Alistipes spp. correlate with human health.